Fucoidan-Doxorubicin Nanoparticles Targeting P-Selectin for Effective Breast Cancer Therapy. (1st December 2020) - Jafari, Mina; Sriram, Vishnu; Xu, Zhenyuan; Harris, Greg M.; Lee, Joo-Youp
Highlights: Fucoidan-conjugated doxorubicin nanoparticles were developed to target P-selectin. Nanoparticles showed uniform sizes, stability, and pH responsiveness. DSPE-PEG helped control and stabilize the size and stability of nanoparticles. NPs showed enhanced cellular uptake in cell line with high P-selectin expression. NPs showed enhanced cytotoxicity against cell line with high P-selectin expression. Abstract: Fucoidan, a type of sulfated polysaccharide known for its anticoagulant, anti-tumor and anti-inflammatory effects, has been reported to have strong affinity towards P-selectin. P-selectin, which plays an important role in metastasis by enhancing the adhesion of cancer cells to endothelium and activated platelets in distant organs, is overexpressed on many cancer types. This study demonstrates the synthesis of a fucoidan-based drug delivery system for minimizing the side effects of doxorubicin (Dox) with the help of active targeting toward P-selectin. Fucoidan-doxorubicin nanoparticles (FU-Dox NPs), developed by direct conjugation of Dox to the fucoidan backbone, showed a well-controlled size distribution and sustained release. The active targeting capability of FU-Dox NPs toward P-selectin resulted in enhanced cellular uptake and cytotoxicity against the MDA-MB-231 cell line with high P-selectin expression compared to the MDA-MB-468 cell line with low P-selectin expression.